2017
DOI: 10.1590/1982-0194201700041
|View full text |Cite
|
Sign up to set email alerts
|

Questionário para avaliação das ações de controle do HIV/Aids na Atenção Básica

Abstract: Objective: To validate the content of a questionnaire to assess the care provided by healthcare professionals to control the HIV/AIDS epidemic in primary care. Methods: A methodological study was conducted, based on the development of a questionnaire using an integrative review, and subsequent validation by experts, using a two-round Delphi technique. Data were analyzed by considering the level of consensus responses, associated with the Kappa index. The criteria for retaining the questions were: ≤ 75% agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…A investigação das circunstâncias envolvidas, dificuldades impostas, (des) motivações dos usuários ou a dinâmica de atendimento, deve promover uma reflexão sobre a necessidade da reorganização dos serviços e melhor orientação dos recursos públicos investidos (Soares;Brandão, 2013), podendo a capacitação permanente para realizar o aconselhamento aumentar para consideravelmente o retorno dos pacientes (Rocha et al, 2017) Research, Society and Development, v. 9, n. 9, e372997126, 2020(CC BY 4.0) | ISSN 2525 Faz-se imprescindível, também, a notificação dos casos de IST, ato realizado por 93% dos participantes. A notificação dos casos de IST é obrigatória à todos profissionais de saúde ou responsáveis pelos estabelecimentos de saúde, públicos ou privados que atuam na assistência ao paciente, segundo a Lei nº 6.259, de 30 de outubro de 1975, e a APS possui um papel importante, pois cabe a esse nível de atenção traçar o perfil epidemiológico da sua realidade para melhor atuar (Silva;Oliveira, 2014).…”
Section: Resultado E Discussãounclassified
“…A investigação das circunstâncias envolvidas, dificuldades impostas, (des) motivações dos usuários ou a dinâmica de atendimento, deve promover uma reflexão sobre a necessidade da reorganização dos serviços e melhor orientação dos recursos públicos investidos (Soares;Brandão, 2013), podendo a capacitação permanente para realizar o aconselhamento aumentar para consideravelmente o retorno dos pacientes (Rocha et al, 2017) Research, Society and Development, v. 9, n. 9, e372997126, 2020(CC BY 4.0) | ISSN 2525 Faz-se imprescindível, também, a notificação dos casos de IST, ato realizado por 93% dos participantes. A notificação dos casos de IST é obrigatória à todos profissionais de saúde ou responsáveis pelos estabelecimentos de saúde, públicos ou privados que atuam na assistência ao paciente, segundo a Lei nº 6.259, de 30 de outubro de 1975, e a APS possui um papel importante, pois cabe a esse nível de atenção traçar o perfil epidemiológico da sua realidade para melhor atuar (Silva;Oliveira, 2014).…”
Section: Resultado E Discussãounclassified
“…(12) Studies have shown that single people have a lower chance of using condoms than married couples. (4) This may influence the increase of infection and transmission risks. They are more promiscuous and less careful about their health because they have to take care of themselves alone.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the goal "90-90-90" was established, which aims to ensure that all infected people are treated by 2020, that 90% of people living with HIV know they have the virus, 90% receive ARVT -Antiretroviral Therapy and 90% of these have viral suppression. (4) Treatment compliance being one of the greatest challenges in care for people living with HIV, it is one of the key pieces to reduce future complications and to improve and prolong the quality of life of individuals affected by the virus. The correct use of the antiretrovirals generates a reduction of costs with future hospitalizations due to complications of the infection, as well as of the necessity to exchange the drug for other more complex and expensive medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Tem a finalidade de possibilitar que este material esteja corretamente elaborado para a sua utilização com a população-alvo (LEITE et al, 2018). A verificação da validade de conteúdo é realizada a partir da inspeção de especialistas, que analisam se as questões que estão dispostas no instrumento irão conseguir alcançar o objetivo proposto (SILVA et al, 2017).…”
Section: Critério De Inclusão Exclusão E Descontinuidadeunclassified